Condicion y ciclo reproductivo de la almeja anodontites trapesialis glaucus (Bivalvia mycetodidae - Cruz, Rafael A.; Courrau, José A. (Uniciencia, 1986)
Condition index, meat percentage and reproductive cycle were studied in a population of Anodontites trapesialis glaucus at Sixaola, Costa Rica, from February 1985 to January 1986. Mean meat percentage was stimed at 55,31% and the mean percentage of the condition index was 62,59 varing from 48,0 in March to 85,0 in September. The monthly variations of condition index and meat showed similar fluctuations. The development and maturation of the lasidium takes place between juny and jannuary. Spawning peaks occurs between February and also in Juny